Anatomical Methods to Study the Suprachiasmatic Nucleus - Bittman, Eric L (Methods in molecular biology (Clifton, N.J.), 2022)
The mammalian suprachiasmatic nucleus (SCN) functions as a master circadian pacemaker. In order to examine mechanisms by which it keeps time, entrains to periodic environmental signals (zeitgebers), and regulates subordinate oscillators elsewhere in the brain and in the periphery, a variety of molecular methods have been applied. Multiple label immunocytochemistry and in situ hybridization provide anatomical insights that complement physiological approaches (such as ex vivo electrophysiology and luminometry) widely used to study the SCN.The anatomical methods require interpretation of data gathered from groups of individual animals sacrificed at different time points. This imposes constraints on the design of the experiments that aim to observe changes that occur with circadian phase in free-running conditions. It is essential in such experiments to account for differences in the periods of the subjects. Nevertheless, it is possible to resolve intracellular colocalization and regional expression of functionally important transcripts and/or their peptide products that serve as neuromodulators or neurotransmitters. Armed with these tools and others, understanding of the mechanisms by which the hypothalamic pacemaker regulates circadian function is progressing apace.